PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - Ade Saputra; Raja Adri Satriawan; Supriono - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This present study was intended to identify the impact of the implementation of government standard accountancy, the system of internal control, and the competency of accounting staff on the quality of the financial statement of the regency government of Kampar. The study was conducted at SKPD governmentof Kampar’ (departments of the regency government of Kampar). The sample was determined using Sampling Purposive Technique and the respondents totaled 96. The data used were the primary data. The data were collected through questionnaire. The data were analyzed using the multiple linear regression analysis assisted with the SPSS version 20.00 program. The result of this study indicated that the government accounting standard ,internal control systemand the human resources competencies and has significantly effect on quality of financial statement. The magnitude of the effect (R2) the government accounting standard, internal control system and the human resources competencies on the quality of the financial statement was 47,7%. While the remaining 52,3% is influenced by other independent variabel that are not observed in this study.Keywords: accounting standard, internal control, competencies, and quality